Influence Merit Pay System in Increasing The Loyalty and Job Satisfaction of Private University Lecturers In Medan - Rizkha Afriani Zulkarnain; Ricky Rafii Ritonga (Institute of Computer Science (IOCS), 2021)
This research is one of the results of lecturers who get ideas in the development of management science especially Compensation Management, to know-how and influence will occur if the variable Merit Pay is linked to the variables of work loyalty and the impact on the job satisfaction of a lecturer of private universities in the city of Medan. The research method used by this research was conducted on PTS lecturers in Medan, with a total of 65 respondents as samples. The research data was obtained through questionaires measured using the Likert scale, and SEM processing was statistically carried out with the help of SMART PLS version 3 with the results of the study showing that there is a significant influence between three variables namely: merit pay, work loyalty, and Job Satisfaction. This research was only conducted at Private Universities in Medan, and research variables are limited to merit pay, loyalty, and job satisfaction. This research shows that there is a relationship between variables, where lecturer performance and loyalty have an impact on the merit pay system.